1995
DOI: 10.2981/wlb.1995.0028
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of a feral cat Felis catus population in an agricultural area of northern Italy

Abstract: The eco logy of a feral cat popul ation in an inten sively cultiv ated region of northern Italy was studied. The study area is a land accretion territory, reclaimed in the early 1970s, characterised by the absence of any food source of human origin (e.g. garbage dumps, farms, houses) and surrounded by a continu ous irrigation channel that is likely to limit immigration/emigration of cats. The cat popul ation was censused for two success ive yea rs using the sighting-resighting method ; spac ing pattern s were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 10 publications
3
20
1
Order By: Relevance
“…Therefore, both euthanasia and TNR would require immigration to be concomitantly controlled or reduced under both scenarios. Our results are consistent with long-term evaluations of TNR colonies that showed population abundance failed to decrease because of immigration (Castillo and Clark 2003) and with studies that showed high rates of transients and population turnover in feral cats (Langham and Porter 1991;Genovesi et al 1995).…”
Section: Discussionsupporting
confidence: 94%
“…Therefore, both euthanasia and TNR would require immigration to be concomitantly controlled or reduced under both scenarios. Our results are consistent with long-term evaluations of TNR colonies that showed population abundance failed to decrease because of immigration (Castillo and Clark 2003) and with studies that showed high rates of transients and population turnover in feral cats (Langham and Porter 1991;Genovesi et al 1995).…”
Section: Discussionsupporting
confidence: 94%
“…One additional factor that may also affect the ranging behaviour of cats that has not been considered in this study is the density of other cats and whether domestic cats are quasiterritorial (feral cats typically are semi-social and territorial: Genovesi et al 1995;Hall et al 2000). If it were the case that range size was negatively affected by cat density, then higher densities of cats may decrease range sizes and indeed this may explain the differences in nocturnal maximum ranging size considered above.…”
Section: Discussionmentioning
confidence: 83%
“…Thus, the habitats surrounding the farms infl uence the habitats available for each cat. In Italy, cats used mainly habitats providing cover but avoided cultivated fi elds (Genovesi et al 1995). In addition in USA, cats often used corridors between habitat patches but fi elds less often than expected by chance (Gehring & Swihart 2003).…”
Section: Habitat Selection and Use Of Individual Speciesmentioning
confidence: 99%